ANALYSIS OF BIOACTIVE COMPONENTS FROM CHLOROFORM EXTRACT OF LYCOPERDON SP. (APIOPERDON) - BHARATHNAIR; ABRAHAM, DELMY; SARANYA, K.; MALLIKARJUNASWAMY, G. E. (Innovare Journal of Sciences, 2021)
Objective: The present work was done to find out various bioactive compounds present in the chloroform extract of Lycoperdon pyriforme using gas chromatography-mass spectrometry (GC-MS). Methods: L. pyriforme was collected cleaned to remove any dirt and oven dried at 60°C. The sample was then finely powdered and extracted with chloroform using Soxhlet apparatus. The chemical composition of chloroform extract was then analyzed using QP2010S-Shimadzu GC-MS instrument. Results: Chloroform extract resulted in the presence of 33 compounds with 1-Heneicosanol (11.17%) and E-15-Heptadecenal (11.08%) forming major compounds and 1-Tetradecanol (0.16%), Dichloroacetic acid, and decyl ester (0.15%) forming least. Conclusion: The results indicated the presence of a variety of compounds thus providing the information about various bioactive compounds present in Lycoperdon sp. and its further application in the field of pharmacology.